PERAN KEUANGAN SOSIAL ISLAM DAN PUSAT PENGEMBANGAN KAMPUNG SDGS INDONESIA DALAM PENCAPAIAN SDGS PENGENTASAN KEMISKINAN DAN KETAHANAN PANGAN: STUDI KASUS DESA SUKOREJO KABUPATEN JEMBER - Ariel Izza Kurnia; Dwi Retno Widiyanti (Islamic Economics and finance in Focus, 2024)
This research aims to examine the role of Islamic social finance, which includes zakah, infaq, sadaqa, and waqf, as well as community empowerment programs conducted by the Center for Sustainable Development Village (PPKSI) in achieving the SDGs goals of poverty alleviation and food security in Sukorejo Village, Bangsalsari District, Jember Regency, East Java. The research was conducted through observation, documentation, and interviews with PPKSI leaders and beneficiaries. Findings indicate that zakah, infaq, sadaqa distributed in the form of business capital assistance, bazaar for poor, scholarships, home renovations, and community empowerment programs such as entrepreneurship training and mentoring, can help achieve the SDGs goals of poverty alleviation and food security. In contrast, waqf practices that indirectly supporting with SDGs goals of poverty alleviation and food security because the waqf assets focus on the education and worship sectors. There is a need for strong synergy among all parties to ensure that the management of Islamic social finance and community empowerment programs positively contribute to SDGs goals, especially in poverty alleviation and food security.